PENGARUH TINGKAT KECUKUPAN MODAL, TINGKAT LIKUIDITAS, DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS BANK KONVENSIONAL DENGAN RISIKO KREDIT SEBAGAI VARIABEL MODERASI - Christine Novrida Anggraini; Belliwati Kosim; Lesi Agusria (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
The purpose of this study was to determine the effect of capital adequacy level on profitability, the effect of liquidity levels on profitability, the effect of operational efficiency on profitability and to determine the effect of credit risk as a moderating variable on the relationship between the level of capital adequacy and profitability, the effect of credit risk as a moderating variable on the relationship between the level of liquidity and profitability, the effect of credit risk as amoderating variable on the relationship between operational efficiency and profitability. In this study, there were 26 samples of conventional banks listed on the Indonesia Stock Exchange for the period 2015-2019 based on the purposive sampling method. The data obtained were then processed using SPSS tools. This analysis included the classical assumption test, moderation analysis with the residual test and t test. The results showed that the capital adequacy level did not have a significant effect on conventional bank profitability listed on the Indonesia Stock Exchange, the liquidity level had no significant effect on conventional bank profitability listed on the Indonesia Stock Exchange, operational efficiency had a significant negative effect on conventional banks profitability listed on the Indonesia Stock Exchange and credit risk were able to moderate the relationship between capital adequacy level and profitability, credit risk was able to moderate the relationship between liquidity evel and profitability, credit risk was able to moderate the relationship between operational efficiency and profitability.Keywords: Capital adequacy level; liquidity level; operational efficiency, profitability and credit risk.